A Prelazia de São Félix do Araguaia e a luta pela terra em Porto Alegre do Norte/Mato Grosso (1970-1980) : migração e conflito no campo - Castravechi, Luciene Aparecida (2017)
This paper analyzes the struggle for land in Porto Alegre do Norte in northeastern Mato Grosso, between the 1970s and 1980. Its object of study conflicts and violence resulting from squatter eviction by agribusinesses - FRENOVA and Piraguassu established in that city during the 1970s, through the Amazon occupation policies by the Government Dictatorial. These projects were overlapping among the lands of rural workers living in the area since the 1940s, so there were disputes over land between these individuals and rural entrepreneurs from the Central South. The Prelature of São Félix do Araguaia, together with pastoral agents, lay, religious and Bishop Pedro Casaldáliga, acted as a mediator in the process of struggle for land, using public powers (Military and Federal Police and the INCRA) and as to the ranch owners and employees so that they could enter into an agreement to demarcate the lands of squatter Porto Alegre do Norte. This process resulted initially in a peaceful negotiation brokered by Dom Pedro Casaldáliga next to FRENOVA, posteriorly the problems and conflicts of squatters against the expulsion of his possessions put the area of the Prelature of São Félix do Araguaia under suspicion this keep subversive elements in their jurisdiction and be combined with the Araguaia guerrilla movement, discovered in 1972 in the region Parrot's beak between southern Pará and northern Goiás (now Tocantins). Thus, in 1973, religious, laity and pastoral agents were kidnapped and imprisoned in the barracks of the 14th Army Police in the city Campo Grande / MS, where experienced days of horror and torture. The struggle for land also involved gunmen, Police Military and Federal Army and the Catholic Church, producing the agrarian issue in Porto Alegre do Norte one spatiality marked by resistance and strategies of rural workers to stay in their possessions.